China and the WHO pandemic treaty: a dive into stance, underpinnings, and implications - Ying Huang; Shisong Jiang; Emmanuel Kumah (Frontiers Media S.A., 2024)
The COVID-19 pandemic exposed gaps in global health governance, catalyzing proposals for a new WHO pandemic treaty. This paper investigates China's stance on the treaty, recognizing it as reflective of many developing countries' concerns, through a qualitative analysis of its interventions during the treaty's drafting and negotiations and an examination of historical and geopolitical factors. Findings reveal China's emphasis on respecting state sovereignty, differentiated obligations for developing nations, preventing stigma, and concrete capacity building-concerns shared across the Global South. Its posture balances pragmatism and principle, reflecting differentiated responsibilities as a major power and developing country along with philosophical divergences from Western legal thinking. While endorsing global cooperation, China insists on voluntary terms without impinging on policy space. Implications suggest that accommodating China's concerns about invasive compliance mechanisms and inequitable burdens through flexible provisions can shape the treaty's acceptance and architecture. Creative solutions reconciling sovereignty and collective action combined with concrete equity measures and depoliticized cooperation will determine the treaty's success. China's major role indicates its endorsement, representative of the Global South's voice, is essential for an impactful pandemic treaty and reformed global health governance.